The Influence of Good Corporate Governance, Maqashid Sharia, and Profitability on Company Value (Empirical Study of Sharia Commercial Banks in Indonesia) - Nadiatul Muna; Muhammad Hafizh; Mukhlish M. Nur (Komunitas Dosen Indonesia, 2024)
The aim of this research is to find out how investors in Indonesia view Sharia Commercial Banks. This is an important step in the capital investment process because it influences the level of trust and confidence investors have in the company. Investors will have more confidence in banks that adhere to sharia principles, including prohibiting usury and speculative practices, and have an active and transparent sharia supervisory board. Therefore, the importance of Maqashid Syariah, profitability, and good corporate governance to company value cannot be overstated. This approach employs a quantitative plan. As study samples, nine Islamic commercial banks were employed. Sharia Commercial Banks employ the ratio scale as one of their data collection tools. The Chow test, Hausman test, Lagrange multiplier test, Classical Assumption test, t test, F test, and Computed R2 test utilizing EViews 10 software all support the multiple linear regression analysis performed in this study. The study's findings demonstrate that, when taken together, profitability, maqashid sharia, and sound corporate governance significantly and favourably affect a company's worth. The results of the partial test also demonstrate that, whilst the profitability variable has a significant negative influence on company value, the Maqashid Syariah variable has a positive and negligible influence.